Law Enforcement Cases of Sexual Violence Against Children - Wardah Nuroniyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Cases of violence against children are still an increasing phenomenon, especially sexual violence. This is because most children who are victims of sexual violence are reluctant to report. As law enforcers and parents should be able to provide an understanding of sex for children so that children do not fall into the wrong hole. This study aims to find out how law enforcement is and the obstacles faced by law enforcers in cases of sexual violence against children. The method used in this study is a qualitative research by describing a description of the social phenomena associated. This type of research is normative law, legal research conducted by examining library materials or secondary data. The obstacle that is often found by the Cirebon City Police, West Java, is the lack of approach between the police and the community so that people are reluctant to report any events that occur to them or around them. Lack of understanding of the community in terms of the process of reporting every event due to lack of socialization. Parents are often silent and afraid to report because sexual harassment is a disgrace to their family.